Court referral and Nigeria's Financial Regulation Advisory Council of Experts (FRACE) - Mustapha, Zakariya; Kunhibava, Sherin; Muneeza, Aishath (International Shari'ah Research Academy for Islamic Finance, 2019)
Purpose: This paper aims to highlight resolution of Islamic finance dispute by common law-oriented courts in Nigeria with respect to Sharīʿah non-compliance and legal risks thereof, as well as the lesson to learn from Malaysia in that regard. This is with view to ensuring Sharīʿah compliance and legal safety of Islamic finance practice as prerequisites for sustainability of the Nigerian Islamic finance industry. Design/methodology/approach: A qualitative method was used; interviews were conducted with different categories of experts and primary data collected in relation to Sharīʿah non-compliance and legal risks in adjudicating Islamic finance dispute by civil courts and the role of expert advice as basis for court referral to Financial Regulation Advisory Council of Experts. A doctrinal approach was adopted to analyse relevant legislative provisions and content analysis of secondary data relevant to applicable provisions in matters of finance before civil courts. Findings: The paper discovers an indispensable role of conventional financial regulations in sustaining Islamic finance industry. Appropriate laws for Islamic finance under the conventional framework foster legal safety and Sharīʿah compliance of Islamic finance activities in related cases handled by courts. Nigeria civil courts can aid sustainability of Islamic finance when so equipped and enabled by laws that address apparent Sharīʿah non-compliance and legal risks in judicial dispute resolution. Inadequate legal provisions for dispute resolution breeds Sharīʿah non-compliance and legal risks in Islamic finance, undermine its prospects and stand inimical to its sustainability. Research limitations/implications: This research is limited by its focus on Sharīʿah non-compliance and legal risks alone, which emanate mainly from judicial resolution of Islamic finance dispute by Nigerian civil courts. Practical implications: This research seeks to motivate a determined and deliberate regulatory action and change in approach towards addressing apparent risks associated with Islamic finance while resolving disputes therein by civil courts. It has implications on common law jurisdictions generally that adopt similar approach as Nigeria's while introducing Islamic finance into their conventional finance framework. Originality/value: Dispute resolution and other regulatory functions of civil courts are important to Islamic finance though apparently overlooked while introducing Islamic finance in Nigeria as in other emerging jurisdictions. This research ascertains the role of the civil courts as indispensable for Islamic Financial Institution (IFIs) operations and demonstrates that such courts are needed for the development and sustainability of Islamic finance industry. The research demonstrates the end-to-end requirement of Sharīʿah compliance of Islamic financial transactions as absolute and needs be ensured and guarded at dispute resolution level by properly equipped courts. © 2019, Zakariya Mustapha, Sherin Kunhibava and Aishath Muneeza.